Geoprocessamento aplicado a detecção de risco de incêndios vegetacionais na Bacia Hidrográfica do Rio Dourados (MG) - (:unkn) unknown (Universidade Federal de Goiás, 2020)
The existence of vegetation fires is considered a threat to biodiversity conservation. There are an agglomeration of reasons for the occurrence of such a fact, such as: lightning, fires caused by anthropic action, burning for cleaning, among others. The fires concern both scientists and environmentalists and also the whole human society, as it causes a series of consequences, the so-called environmental impacts, where these impacts happen due to the recurrent incidence of vegetation fires in a given region. After the fires, one of the great damages that occur is the loss of vegetation and, in a sequential way, after the loss of the leaves, the soil is exposed and subsequently can result in soil erosion. With erosion there is a load of sediment in the waters during the rainy season, which can lead to the silting up of rivers. These impacts occur in a sequential manner, harming the entire area. The great occurrence of vegetation fires in the BHRD (Rio Dourados Hydrographic Basin - MG) area, has been of great concern to the region's residents, mainly because the basin's economy is based on the activity of agriculture and livestock where vegetation fires cause a series of damage to local populations. Thus, there is a need to map the areas with the highest risk of vegetation fires and the environmental impacts caused by fire. In order to arrive at this risk mapping, a modeling of climatic and topographic variables that are of natural origin and variables, which originate from anthropic action, is made. Through this mapping it is possible to see if in the basin area there is a risk of vegetation fires. For this, geotechnologies were used, including Geoprocessing and GIS, and for the identification of environmental impacts, fieldwork was used. The results found were the risk mapping for each of the variables used, the final risk that was obtained by crossing these variables, with BHRD having as a predominant class the Medium Risk with 94.45% of the entire area. The other areas are: 2.69% with high risk and 2.86% with low risk of vegetation fires. In relation to environmental impacts, loss of vegetation, impacts on rural properties and fauna were identified through fieldwork. The others, such as soil erosion and silting up the Dourados River, found that this type of impact happens not only due to fires, but also due to other causes acting together. Even though BHRD has the Medium Risk class as its predominant class, the basin suffers from constant Vegetal Fires, these fires being of great proportions. Most of these fires are intentional, that is, they are caused by the human being. So a way to prevent it would be to raise the awareness of the entire population, as the best way is to prevent the fire from starting than to control it, because the basin has great fire propagation capacity.
Geoprocessing applied to the risk detection of plant fire in the Dourados River Hydrographic Basin (MG)
Keywords: Incêndio vegetacional; Riscos; Bacia hidrográfica do Rio Dourados; Impactos ambientais; Vegetational fire; Scratchs; River Dourados hydrographic basin; Environmental impacts; CIENCIAS HUMANAS::GEOGRAFIA